Comparison of ligase chain reaction and culture for detection of Neisseria gonorrhoeae in genital and extragenital specimens. - Stary, A (1997)
In addition to the urogenital tract, Neisseria gonorrhoeae infects extragenital sites such as the pharynx and anorectal canal. Culture and a ligase chain reaction (LCR)-based assay were compared for their performance for the diagnosis of N. gonorrhoeae infection with specimens from various urogenital and extragenital sites of 200 men and 125 women. The sensitivity and specificity of the LCR assay with male urethral swabs were both 100%, compared to values of 95.9 and 100%, respectively, for culture of urethral swabs or 98.0 and 100%, respectively, for LCR with first-void urine (FVU). For women, LCR with FVU showed the highest sensitivity (94.7%), and culture of urethral samples showed the lowest sensitivity (63.2%) (P < 0.05). In a selected subgroup of 47 men and 22 women at increased risk, the rates of pharyngeal infection were 15 and 18%, respectively, and those of anorectal infection were 13 and 45%, respectively. The sensitivity of LCR was greater than that of culture for both pharyngeal and anorectal specimens. Thus, the overall performance of LCR testing with swabs or FVU was better than that of culture for the diagnosis of genital or extragenital gonorrhea.